The SEMIOTIC ANALYSIS ON THE VERSES OF ANAK DIONG SONG BY FELIX EDON - Baptista Angelino Galus, Yohanes (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2025)
This research delves into the semiotic analysis of Felix Edon's song Anak Diong, examining its meaning through heuristic and hermeneutic readings. It underscores the centrality of communication in human interaction and the diverse mediums, with music serving as a universal language to express sentiments and to convey messages. Specifically focusing on Manggaraian culture, the text elucidates how music, including the addition of Manggaraigo’et (proverbs), reflects deep-rooted values and philosophies. The methodology involves qualitative analysis of the song lyrics, drawing from both primary data, obtained from interviews and literature studies, and secondary data from relevant sources. Through heuristic reading, the verses are dissected linguistically, revealing layers of meaning and emotional resonances. A hermeneutic reading then delves deeper into the contextual and symbolic significance, offering interpretations based upon literary conventions and cultural insights. The song Anak Diong emerges as a poignant narrative of an abandoned child grappling with identity and longing for parental love. It transcends individual experiences to underscore broader societal issues, urging responsible parenthood and resilience in adversity. The Manggarai language and cultural references imbue the lyrics with profound meaning, resonating with audiences beyond linguistic and cultural boundaries. Ultimately, the text underscores the transformative power of music to convey profound messages and evoke empathy, making Anak Diong a poignant reflection of human experiences and values.